Changes with time post-restoration in the relationships between soil seed bank and aboveground vegetation in a reclaimed open-pit coal mine - Yiming Liu; Le Qi; Weibo Ren; Zhe Chen; Feng Yuan; Yaling Liu (Scientific Reports)
Abstract The soil seed bank (SSB) is a potential resource for the aboveground vegetation community (AVC) and plays a crucial role in ecological restoration. Studying the succession of the SSB and AVC at different restoration stages provides valuable insights into their temporal dynamics, facilitates comprehensive investigations of the different restoration stages, and enables appropriate recommendations for the subsequent restoration to be provided. Therefore, the SSB and AVC of restored grassland ecosystems were investigated in open-pit coal mine dumping sites in a typical grassland area of Inner Mongolia. This study was therefore conducted in a typical grassland with the same restoration practices (mixed seeding of Gramineae and Leguminosae), and comparisons were made at different periods post-restoration to determine the pattern of changes in the SSB and AVC over time post-restoration. Through non-metric multidimensional scaling (NMDS), a correlation analysis, and structural equation model, the changes in the SSB and AVC in the years following restoration were determined. It was found that the SSB density was 475.00 − 705.00 (plant m− 2), and the AVC density was 94 − 192.8 (plant m− 2). Notably, a significant shift occurred 17 years post-restoration, indicating a pivotal stage was reached in the overall trajectory of the SSB and AVC. The vegetation in the restored area was found to be transitioning toward natural grassland, with an increase in the proportion of perennial species and a gradual decrease in annual and biannual species. The density of Gramineae and Leguminosae plants was similar to that of natural grasslands 17 years post-restoration. The presence of the invasive species Salsola collina gradually decreased over time. The relationship between soil physicochemical properties and SSB was relatively weak, while the relationship with AVC was relatively strong. With time post-restoration, the resemblance between the SSB and the plant community slowly diminished at the mining dump. The study provides for the prolonged rehabilitation of open-pit coal mine dumping sites.